2020
DOI: 10.9734/arrb/2020/v35i730251
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Anti-diabetic Activity of Phenylquinoline, and Narceine Isolated from Ficus polita Leaf

Abstract: The present study was conducted to evaluate anti-diabetic potentials of column chromatography fractions (F1-F6) of chloroform leaf extract of Ficus polita and to detect the probable bioactive compounds present in the most active fraction using spectroscopic techniques. Antidiabetic potential of the fractions (F1-F6) were tested at a dose of 50 mg/kg on wistar rats. Fraction 3 and metformin treated diabetic groups showed significant decreases in fasting blood glucose (FBS) level, ameliorate hepatic and renal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, ( Stephen Irudayaraj et al, 2017 ) concluded that Ficus carica leaves showed hypoglycemic and hypolipidemic activities in streptozotocin (STZ)-induced T2DM in rats and considerable effect on the enzymes of carbohydrate metabolism. ( Nasir et al, 2020 ) stated that the methanolic extract of F. carica showed hepatoprotective activity against medicine-induced hepatotoxicity. Olea europaea is one of the most important and oldest cultivated plants; it is the sixth most important oil crop worldwide, olive oil has a high economic value and profitable nutritional characteristics ( Reale et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ( Stephen Irudayaraj et al, 2017 ) concluded that Ficus carica leaves showed hypoglycemic and hypolipidemic activities in streptozotocin (STZ)-induced T2DM in rats and considerable effect on the enzymes of carbohydrate metabolism. ( Nasir et al, 2020 ) stated that the methanolic extract of F. carica showed hepatoprotective activity against medicine-induced hepatotoxicity. Olea europaea is one of the most important and oldest cultivated plants; it is the sixth most important oil crop worldwide, olive oil has a high economic value and profitable nutritional characteristics ( Reale et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%